Improving Performance Stability of Power System Java-Bali Interconnection with PIDPSS3B and PIDSVC Controllers - Manuaba, Ida Bagus Gede; Mertasana, Putu Arya; Mataram, Made; Partha, Cok Gede Indra (Journal of Electrical, Electronics and Informatics, 2017)
Modern electric power system that many its dynamic equipment continuously vulnerable to internal and external disturbances. On the condition of the disorder, it often happen oscillation in each part or between parts of the electrical system is interconnected. These oscillations become a major problem for the stability of the power system. Modern electrical control systems require a sustainable balance between power generation and demand varying loads. Power System Stabilizer and Static Var Compensator is a control device that is used to dampen low frequency oscillations and to provide additional feedback signal to stabilize the system. To increase the damping, system equipped with PSS generator that provides additional feedback to stabilize the signal in the excitation system. It is generally that the machine parameters changed by the load, so the dynamic behavior of the different machines at different operating conditions. Design PIDPSS3B power system stabilizer and PIDSVC controller used aim to get performance and optimum damping. Design and optimization of the proposed has the ability to optimally dampen and suppress errors are minimal.